Outcome of Colpoclesis in Advanced Pelvic Organ Prolapse in Elderly Women (Bangladesh Medical Journal, 2019)
To find out the safety, effectiveness and outcome of colpocleisis in advanced pelvic organ prolapse in elderly women. A prospective study was conducted in Sheikh Hasina Medical College,Tangail (250 beded general hospital,tangail) among 75 female patients aged 60 years and above with diagnosed cases of Pelvic Organ Prolapse (POP) during the period from February 2014 to February 2018 who had no desire in coital function. Patient information were recorded pre-operative, per-operative and post-operative period. Urodynamic investigation (uroflometry and post void residual urine) were done during pre-operative  and early postoperative period. Follow up was done at 6 week, 3 month and then annually. Main outcome measures were relieving symptoms, recurrence of prolapse and development of urinary incontinence. Patient satisfaction (Subjective outcome) measured by interview during follow up. Colpocleisis was performed in 75 patients. Mean (age of the patients was 66.69 SD ±5.9 years, mean BMI 18.12 SD ±1.69 kg/m2 and mean parity 5.56 SD ±1.9. Majority of operation done under saddle block, only 21.31% was done under local anaesthesia. Mean operation time was 36.16 SD±6.23 minutes, mean blood loss was 41.61 SD±8.34 ml and mean hospital stay was 2.24 SD ±0.49 days. Objective and subjective outcome were same 98.7% only 1.3% patient developed recurrent prolapse (Failed operation) and 1.3% patient developed urinary urge incontinence. The mean differences were significant for the pre and postoperative maximum urinary flow rate, voided volume, post void residual urine (P value is 0.001). Colpocleisis is safe, effective with high success rate in the management of advance pelvic organ prolapse, who do not wish to preserve coital function. So it can be considered as one of surgical option for treating advance pelvic organ prolapse.Bangladesh Med J. 2018 May; 47 (2): 17-22